2019
DOI: 10.1080/02670844.2018.1512198
|View full text |Cite
|
Sign up to set email alerts
|

Wear behaviour of boronized and duplex-treated AISI 4140 steel against DLC-coated boronized AISI 4140 disc

Abstract: Wear behaviour of the AISI 4140 steel specimens with various surface conditions was tested against the DLC-coated boronized disc of AISI 4140 steel. Specific wear rate and coefficient of friction (COF) of the as-boronized (AB) pins at 100 and 150 N loads were substantially lower than the boronized-polished (B-P) pins. COF of AB pins was in the range of 0.07-0.09. However, the COF of B-P pins was about 0.13. In case of the DLC-coated pins, underlying boronized surface outperformed the hardened-tempered surface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Diamond-like carbon (DLC) films, transition metal nitride and carbide films that are prepared on cutting tools and drillings have been applied to improve their properties. [1][2][3][4][5] However, the DLC films, especially, tetrahedral amorphous carbon (ta-C) films, have attracted considerable interest in properties comparable with those of nitride and carbide films, such as high hardness, low friction coefficient, excellent wear resistance, and anti-affinity with wear debris. [6][7][8][9] Among the many preparation methods for DLC films, the filtered cathodic vacuum arc (FCVA) technique is an effective and common method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diamond-like carbon (DLC) films, transition metal nitride and carbide films that are prepared on cutting tools and drillings have been applied to improve their properties. [1][2][3][4][5] However, the DLC films, especially, tetrahedral amorphous carbon (ta-C) films, have attracted considerable interest in properties comparable with those of nitride and carbide films, such as high hardness, low friction coefficient, excellent wear resistance, and anti-affinity with wear debris. [6][7][8][9] Among the many preparation methods for DLC films, the filtered cathodic vacuum arc (FCVA) technique is an effective and common method.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid and high‐quality development of the manufacturing industry, better performance of micro‐cutting tools and drillings that can be used in the medical, printed circuit board (PCB) and motors are more in demand. Diamond‐like carbon (DLC) films, transition metal nitride and carbide films that are prepared on cutting tools and drillings have been applied to improve their properties 1–5 . However, the DLC films, especially, tetrahedral amorphous carbon (ta‐C) films, have attracted considerable interest in properties comparable with those of nitride and carbide films, such as high hardness, low friction coefficient, excellent wear resistance, and anti‐affinity with wear debris 6–9 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, Jeyaraj et al [6] found that the amount of particle reinforcement and its distribution homogeneity plays a vital role in the functional properties of the composite coating. The different nano particles used in the Ni matrix coating are SiC [5,7], Al 2 O 3 [8], ZrO 2 [9], TiO 2 [10,11], SiO 2 [12], B 4 C [13], Si 3 N 4 [14], CNT [15], TiC [16], diamond like carbon (DLC) [17], etc. The enhanced properties and low cost of Al 2 O 3 particles in Ni matrix coating made it more popular.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to mineral oil, the Jatropha raw oil reduced both friction and wear for AISI1040 samples. Litoria et al [ 13 ] studied the wear behavior of AISI4140 steel samples with various surface conditions sliding against DLC-coated boronized discs of AISI4140 steel. Singh et al [ 14 ] studied the tribological behavior of shot-peened quenched-tempered SAE-6150 steel specimens.…”
Section: Introductionmentioning
confidence: 99%